Enhancing Urban Mobility Efficiency Through Intersection Coordination in the Context of Sustainable Urban Development - Sri Sarjana; Andrean Izza Maulana (Jurnal Pembangunan Wilayah dan Kota, 2026)
Intersection coordination is a strategic approach in traffic management that aims to manage signal timing in an integrated manner at several adjacent intersections to improve the smooth flow of vehicles. This study focuses on evaluating the performance of intersection coordination using Transyt software as an optimization tool. The study was conducted at two major intersections, namely the Stadion intersection and the RSUD Sayyidiman intersection in Magetan Regency, Indonesia, which are experiencing increasing traffic activity as the area grows. Before coordination, both intersections showed levels of delay, queue length, and saturation levels that indicated a decrease in mobility efficiency. Through a process of optimizing cycle times and signal phases, a green wave system was implemented between intersections to smooth the movement of vehicles within a single corridor. The results showed significant improvements in intersection performance, including reduced delays, shortened queues, and an overall increase in the level of service. This study confirms that intersection coordination not only improves the efficiency of urban mobility but also contributes to the goal of sustainable urban development by reducing the environmental impact of congestion and excessive fuel consumption.